Bluey. Rug Island [compact disc]. - Bush, Joff (Crimson Productions, 2024)
The follow up to Dance Mode! Features sixteen brand new recordings from series one, two and three. It is an album of adventure, a playful journey through the imaginations of Bluey and Bingo. The album takes inspiration from the episode Rug Island, a place where children play and adults embrace their inner kid.